2017
DOI: 10.18681/pjn.v35.i01.p79-84
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of six leguminous crops against the root-knot nematode, Meloidogyne javanica infection

Abstract: Twenty seven leguminous cultivars were tested for their host response to Meloidogyne javanica. The nematode species succeeded in developing and multiplying on almost all the tested crops. According to rating scale based on nematode reproduction, Lencoln and Victory cultivars of pea were considered as highly susceptible hosts with (R f) values 36.5 and 25.68 folds, respectively. While Maser-1 cultivar of broad bean and Bronco, Exira, Giza-6, Polista and Savana cultivars of common bean were classified as moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…According to Oostenbrink (1966), the cultivation of a resistant cultivar may suppress the nematode population by 10-50% of its harmful density. Susceptibility of different pulse crops has been reported by sev-eral researchers such as Pandey et al (2016) and Montasser et al (2017). Sasser (1954) found that the roots of resistant plants were not invaded as rapidly as susceptible ones.…”
Section: Introductionmentioning
confidence: 98%
“…According to Oostenbrink (1966), the cultivation of a resistant cultivar may suppress the nematode population by 10-50% of its harmful density. Susceptibility of different pulse crops has been reported by sev-eral researchers such as Pandey et al (2016) and Montasser et al (2017). Sasser (1954) found that the roots of resistant plants were not invaded as rapidly as susceptible ones.…”
Section: Introductionmentioning
confidence: 98%
“…Faba bean (Vicia faba L.) is a major grain legume widely cultivated in many countries for food and feed purposes [2], and it is one of the oldest legume crops grown in Egypt. The root-knot nematode species attack the roots of the crops and considerably reduce the yield of legumes [3]. Chemical treatment using different types of nematicides has been proposed for the management of root-knot nematodes.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of nematode reproduction was calculated. The host category of the tested potato cultivars infected with M. javanica based on nematode reproduction (Pf/Pi) was determined according to Montasser, et al (2017) as follows: (Pf / Pi = 0.0) I = Immune host; (Pf / Pi < 0.4) HR = Highly resistant host; (0.5 ≤ Pf / Pi ≤ 0.9) R = Resistant host; (1.0 ≤ Pf / Pi ≤ 4.9) LS = Less susceptible host; (5.0 ≤ Pf / Pi ≤ 14.9) MS = Moderately susceptible host and (Pf / Pi > 15.0) HS = Highly susceptible host. Also, the potential of each cultivar to support egg production of R. reniformis was calculated in relation to that of Burren potato cultivar which was regarded as a check potato cultivar and host category, based on percentage of egg production of each potato cultivar was estimated according to that scale given by Montasser (1986) as follows: 0%= Immune (I), 1-10%= Highly resistant(HR), 11-20%= Resistant (R), 21-40%= Less susceptible (LS), 41-60%= Moderately susceptible (MS), and 61-100%= Highly susceptible (HS).…”
Section: Methodsmentioning
confidence: 99%